Mortality Risk during Heatwaves: an Evaluation of Effects by Heatwaves Characteristics in Serbia - J. Allen, Michael; Arsenović, Daniela; Savić, Stevan; Nikitović, Vladimir (Geographica Pannonica, 2024)
Extreme temperatures and heatwaves are recognized as one of the deadliest weather-related hazards. The first of its kind in the Balkans region, this study explores the effects of heatwave timing, duration, and intensity on mortality in Serbia. Using daily all-cause mortality data and mean temperature, a distributed lag non-linear model (DLNM) evaluates the heat-mortality response for each city during the warm season (May to September) for the period 2000-2015 for Belgrade, Novi Sad and Niš. Results indicate that longer heatwaves generally have a greater impact on mortality, regardless of when they occur in the warm season. When comparing warm and extremely warm days, relative risk (RR) increases with intensity, and RRs are higher for earlier season heatwaves Extremely warm, early season heatwaves show significantly high RR in all three cities, respectively, for Belgrade 1.37 (95% CI: 125, 1.5), for Novi Sad 1.27 (95% CI: 1.08, 1.5), and for Niš 1.47 (95% CI: 1.15, 1.87). The findings draw attention to how different heat events modify the health response in Serbia. Stakeholders who work to improve resilience to heat hazards may consider the development of an early warning heat system and a strengthening of local and regional outreach efforts designed to reduce adverse health outcomes.